2019
DOI: 10.1088/2399-6528/ab3c1c
|View full text |Cite
|
Sign up to set email alerts
|

Causality in quantum field theory with classical sources

Abstract: In an exact quantum-mechanical framework we show that space-time expectation values of the second-quantized electromagnetic fields in the Coulomb gauge in the presence of a classical conserved source automatically lead to causal and properly retarded ÿ-independent electromagnetic field strengths. The classical ÿ-independent and gauge invariant Maxwell's equations naturally emerge in terms of quantum-mechanical expectation values and are therefore also consistent with the classical special theory of relativity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 59 publications
0
19
0
Order By: Relevance
“…In the present paper we extend the work of Ref. [1] to linear gravitational quantum deviations around a flat Minkowski space-time in a Coulomb-like gauge in the presence of a classical and conserved energy-momentum tensor. The time-evolution as dictated by quantum mechanics, for a suitably defined second-quantized gravitational field, then automatically solves the issues of causality and retardation in a similar manner as in the case of electro-dynamics.…”
Section: Introductionmentioning
confidence: 56%
See 3 more Smart Citations
“…In the present paper we extend the work of Ref. [1] to linear gravitational quantum deviations around a flat Minkowski space-time in a Coulomb-like gauge in the presence of a classical and conserved energy-momentum tensor. The time-evolution as dictated by quantum mechanics, for a suitably defined second-quantized gravitational field, then automatically solves the issues of causality and retardation in a similar manner as in the case of electro-dynamics.…”
Section: Introductionmentioning
confidence: 56%
“…In a previous publication [1] we have shown that the time-evolution as dictated by quantum mechanics, for second-quantized electro-magnetic fields in the presence of a classical conserved electric current, automatically solves these issues. The classical theory of Maxwell then naturally emerges in line with more general S-matrix arguments due to Weinberg [11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from an overall factor, the interference pattern will therefore be the same for a source prepared in, e.g., a quantum-mechanical Fock-state of photons or for a conventional coherent state. As is well-known, the use of coherent states naturally leads to the interference of classical electro-magnetic fields (see, e.g., [13] and references cited therein). The observation of a non-zero value of κ S is therefore not exclusively related to quantum-mechanical interference effects.…”
Section: Introductionmentioning
confidence: 99%